Second language acquisition in a study abroad context - Freed, Barbara F. (Studies in bilingualism, 1995)
Second Language Acquisition in a Study Abroad Context brings together for the first time a series of studies which explore the relationship between language learning and the study abroad experience. Utilizing different research methodologies (quantitative, qualitative, descriptive), the focus in this collection is on various aspects of second language learning, including the acquisition of sociolinguistic competence, the acquisition of fluency, the use of communicative strategies and the development of oral and written skills. The studies are cross-linguistic and deal with student populations.